THE GLOBAL TASKS OF ENGINEERING EDUCATION AND ENGINEERS’ TRAINING AT NATIONAL RESEARCH UNIVERSITY - German S. Dyakonov (Высшее образование в России)
The paper explores the topical tasks of engineering education and considers the ways to solve them both on national basis and on the level of a research university. Engineers’ training requires applying of new approaches such as interdisciplinary and transdisciplinary. The technical university of XXI century must be a transdisciplinary university, and engineers’ education should include training of specialists at enterprises and companies. The other measures include realization of the universities’ own education programs and standards, creating of a network of lycees, and introducing of obligatory unified state examination in physics, chemistry, and biology.